Cânticos de cura dos Kariri- Xocó - Câmara Neto, Ruy Rodrigues (2016)
This work is an ethnomusicological research about the healing music of the Kariri-Xocó people - an indigenous communitylocated in the cityof Porto Real do Colégio in the state of Alagoas. This people present a cosmology that is characterized by the understanding of terrestrial life being governed bysomethingvastlylarger and more powerful than them - the Source. In this world inhabited by divine forces, the reverence of the Kariri-Xocó is manifested in various aspects of social life, which has more expressive traits in their religious rituals, where music takes on a central role. Our main goal in this research was to analyze the role of music, especially the healing songs performed within the Toré. The study shows that the music performed by the Kariri-Xoco, in its various contexts, either with or without the use of entheogens (power plants) aims the expansion of consciousness to other cosmological levels and the consequent meeting with the Source.